The Investigation of Mudrock Disintegration: Case Study at Hambalang Area, Bogor, West Java - Misbahudin - (Jurnal Geologi dan Sumberdaya Mineral, 2023)
Many infrastructure buildings are on mudstone. The Hambalang area is an area that has projected infrastructure buildings such as the Puncak II road that is projected to connect the Bogor-Cianjur strategic area. Engineering issues may stem from a hazardous material related to existing mudrock. Mudrock can be studied through the disintegration behavior of wetting and drying processes. The research examined the mudrock disintegration of several samples in the studied area. Outcrops in the field were recorded and then sampled by the standard pack. This test mainly needs rock samples weighing 450-550 grams, dried in the sun for the length of the day. The sample was then immersed in a glass filled with water for 1 x 24 hours. The standard properties tests were also carried out to obtain such physical parameters from moisture content, dry density, and void ratio, until absorption. According to the disintegration parameter, the sample explicitly indicates the massive disintegration of each cycle. Most of the samples started to experience a marked disintegration after the first cycle and have mostly fragmented to an angular shape. With the application of the correlation line, dry density significantly affects the mudrock disintegration.